2020
DOI: 10.1177/2150132720946948
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Non-communicable Diseases—A Wake-up Call for Primary Health Care System Strengthening in Sub-Saharan Africa

Abstract: Strengthening Primary Health Care Systems is the most effective policy response in low-and middle-income countries to protect against health emergencies, achieve universal health coverage, and promote health and wellbeing. Despite the Astana declaration on primary health care, respective investment is still insufficient in Sub-Sahara Africa. The SARS-CoV-2019 pandemic is a reminder that non-communicable diseases (NCDs), which are increasingly prevalent in Sub-Sahara Africa, are closely interlinked to the burde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…As early as 2007, a call was made to strengthen preparedness for a highly pathogenic influenza like pandemic in Africa (6). More recently, the COVID-19 pandemic has led to the realization for the need to strengthen primary health care systems (7). Community health workers (CHWs) play a critical role in primary health care systems in sub Saharan Africa, and their role in pandemics is increasingly being recognized: Corburn et al recommended immediate training and deployment of CHWs to address COVID-19 in informal settlements of the global south (8).…”
Section: Introductionmentioning
confidence: 99%
“…As early as 2007, a call was made to strengthen preparedness for a highly pathogenic influenza like pandemic in Africa (6). More recently, the COVID-19 pandemic has led to the realization for the need to strengthen primary health care systems (7). Community health workers (CHWs) play a critical role in primary health care systems in sub Saharan Africa, and their role in pandemics is increasingly being recognized: Corburn et al recommended immediate training and deployment of CHWs to address COVID-19 in informal settlements of the global south (8).…”
Section: Introductionmentioning
confidence: 99%
“…Allel et al (2020) find that a delay in the government lockdown responses significantly affected the incidence rate ratios (IRR) of COVID-19 cases. Health care capacity of a country is another important determinant of pandemic preparedness (Chaudhry et al, 2020;Khan et al, 2020;Kraef et al, 2020;Mbunge, 2020). Health inequalities due to inadequate health capacity, directly affect vulnerable people (Bambra et al, 2020).…”
Section: Introduction I Introductionmentioning
confidence: 99%
“…The quality of food and nutrition has crucial role in NCDs-COVID-19 prevention. But in COVID 19 episode measures reported to limit the accesses and availability of healthier foods and also limit physical activity (8). However, many nutrition studies have been directed to individually dietary intakes of which it is different from this.…”
Section: Discussionmentioning
confidence: 99%
“…But, recently, few studies demonstrated climate changes events; extreme weather changes, air pollution, increase of industrial activities, ood and storms are among of risk factors (6,7). Moreover, NCDs and COVID 19 are sharing the risk factors, like inadequate fruits and vegetables intake, excessive intake of alcohol, physical inactivity, air pollution and overpopulation , high intake of trans-fat, salt, as well tobacco use (8,9) and this is the signi cant of this study on NCDs-COVID 19 prevention.Besides, the combinations of these two diseases have increased the burden to people's life. NCDs itself kills about 70% people worldwide annually, while 2/3 of them are from developing countries, In 2016, the NCDs reported to kill 71% worldwide, among of them, 4% were young people below 30 years, whereas 38% were people with the age between 30 -70 years and 58% were people with 70 years and above.80% of deaths were due to cancers, cardiovascular diseases, chronic respiratory diseases, and diabetes and 20% were from slow NCDs killer (10).…”
mentioning
confidence: 96%